The Emerging Roles of Academic Librarians in the Electronic Information Environment at Kwame Nkrumah University of Science and Technology (KNUST), Kumasi (Journal of Science and Technology, 2016)
This paper discusses the traditional and emerging roles of the academic librarian. It sees the traditional roles as functions that have enabled the librarian to provide the needs of his clientele mostly within the walls of the academic library. It also enumerates and expatiates on the roles of the academic librarian in the Electronic Information Age with its attendant explosion of knowledge. It emphasizes the fact that infrastructural boundary is virtually non-existent in provision of information today. Finally, it uses the situation of the KNUST to establish parallelism between the conventional and emerging roles of the academic librarian and also the importance of library professionals in information provision.